Performance characterization of low-cost, high-speed, portable pulsed laser diode photoacoustic tomography (PLD-PAT) system - Upputuri, Paul Kumar (2015)
Photoacoustic tomography systems that uses Q-switched Nd:YAG/OPO pulsed lasers are expensive, bulky, and hence limits its use in clinical applications. The low pulse repetition rate of these lasers makes it unsuitable for real-time imaging when used with single-element ultrasound detector. In this work, we present a pulsed laser diode photoacoustic tomography (PLD-PAT) system that integrates a compact PLD inside a single-detector circular scanning geometry. We compared its performance against the traditional Nd:YAG/OPO based PAT system in terms of imaging depth, resolution, imaging time etc. The PLD provides near-infrared pulses at ~803 nm wavelength with pulse energy ~1.4 mJ/pulse at 7 kHz repetition rate. The PLD-PAT system is capable of providing 2D image in scan time as small as 3 sec with a signal-to-noise ratio ~30. High-speed and deep-tissue imaging is demonstrated on phantoms and biological samples. The PLD-PAT system is inexpensive, portable, allows high-speed PAT imaging, and its performance is as good as traditional expensive OPO based PAT system. Therefore, it holds promises for future translational biomedical imaging applications.